Influence of sediment distribution on the relationships among reservoir yield, spill, and evaporation losses - Campos, Jody (2018)
This study shows how the sedimentation process in reservoirs affects the yield-spill-evaporation losses in reservoirs of Ceará State, Brazilian Northeast. Reservoirs are assumed to have, initially, inverted conical shape. Three forms of sedimentation were investigated: type 1, with deposition occurring parallel to the wetted perimeter; type 2, deposition distributed proportionally to the water depth; and, type 3, deposition concentrated in the reservoir bottom. These sedimentation patterns were found in many reservoirs in Ceará, with capacity ranging from about 0.5 to 100 hm3. Nevertheless, type 2 pattern was the most frequent. In this paper, five large reservoirs, over 100 hm3, were studied using Monte Carlo approach, and considering the silting over the time horizon. It was found that sediment distribution can significantly affect the yield-spill-evaporation trade-off on large reservoirs. Type 1 results have the lowest impact on reservoir yield, followed by type 2 and type 3. For Cedro reservoir, the yield would go to zero in 2115, assuming a type 3 deposition pattern. These results reinforce the need for monitoring sedimentation in large reservoirs in the Brazilian semiarid region. In addition, this study provides a relatively simple methodology to predict the impact of siltation on reservoir yield-spill-evaporation relationships, for the three most found patterns of sedimentation.